Analisis Sambungan Las pada Bahan Copper-Nickel dan Nickel-Chromium Iron Alloys dengan Proses GTAW - A Yudia Bakti; Surasno Surasno (Center for Material and Technical Product, 2014)
Welding joint of copper-nickel to Nickel-chromium Iron Alloys had been problem in penetration and mechanical properties. In order to get a good quality of welding, welding design of copper-nickel to Nickel-chromium Iron Alloys using heat input 2145 to 4680 J/cm. The results are good welding joint penetration to wide bevel and vertical joint. Namely, the structure of welding joint area has no imperfection and mechanical properties of welded metal are better than the base metal. That’s are tensile strength 46.56 kg/mm2, elongation 31.25%, reduction of area 33.10%, and fracture area in fusion line weld of Copper-Nickel has no defect. Besides, bending test result has showed no crack. In addition, the hardness values are variably shown such as 128,3-137,9 VHN in the HAZ Copper-Nickel, 177-195 VHN on Weld Metal, and 195-210 VHN on HAZ of Nickel-Chromium. Based on the results above, the welding of Copper-Nickel to Nickel-Chromium Iron Alloys Steel could be applied in joining heat exchanger equipment in industries. Sambungan las dissimilar material Copper-Nickel terhadap baja Nickel-Chromium Iron Alloys mempunyai permasalahan pada penetrasi dan sifat mekanis. Telah dilakukan rancangan pengelasan bahan Copper-Nickel terhadap Nickel-Chromium Iron Alloys dengan parameter Heat input (2145 s.d 4680) J/cm untuk menghasilkan sambungan las yang baik tanpa cacat-cacat las. Hasil pengelasan menunjukkan penetrasi logam las pada sisi bevel dan arah vertical baik, struktur makroskopis penampang sambungan las tidak terdapat cacat-cacat las, sifat-sifat mekanis: kuat tarik 46,56 kg/mm2, nilai regang 31,25%, reduksi penampang 33,10%, dan putus di fusionline las Copper-Nickel tidak terdapat cacat las. Hasil uji lengkung tidak retak. Nilai kekerasan di HAZ Copper-Nickel cenderung beragam (128,3-137,9)VHN, di logam las (Weld Metal) pada rentang kekerasan 177-195 VHN, dan HAZ Nickel-Chomium berkisar 195-210 VHN. Pada dua bahan ini struktur mikro terjadi struktur dendritic dan epitaxial di sekitar fusion line. Sambungan las Copper-Nickel terhadap baja Nickel-Chromium Iron Alloys telah menunjukkan hasil pengelasan GTAW yang baik dan dapat digunakan pada pemakaian sambungan las peralatan penukar panas di industri.